FINANCIAL INCLUSION FOR INCLUSIVE GROWTH WITH REFERENCE TO INDIA’S BUSINESS ENVIRONMENT - Tiwari, Dr. Shweta; Deshmukh, Dr. Sanchet Singh (The journal of contemporary issues in business and government, 2023)
With 1.41 billion people, more than 900 million people spread around more than 6 lac villages. In the post liberalization period especially during 2003-04 to 2007-08, the Indian economy witnessed high growth. The major drivers of high growth have been LPG policies, improvement in economic and social infrastructure, IT industry, increasing entrepreneurship and many other factors that were transforming India into a major emerging economy. But this growth has been uneven and discrete. The progress in growth has not been uniform and the benefits of growth went to certain sections of the society and by passed marginalized and vulnerable sections of the society. This growth has been termed as jobless growth and has increased regional inequalities. Poor have become more poorer and the divide between urban and rural has increased. India is still the home of world's largest number of poor and under-nourished children. Indian Rural economy constitutes around 46 % of national income. The study highlights the profound changes experienced by India’s rural economy and employment This paper is an analytical effort in the area of financial inclusion and inclusive growth and also provides insight into India’s business context.